FACTORS AFFECTING THE COMPETITIVENESS OF POSTAL BUSINESSES: A VIETNAM SURVEY - Thi Quyen, Bui; Thi Mai Huong, Nguyen; Quoc Dat, Luu; Mai Phuong, Pham; Khanh Ly, Le Thi; Thuong, Le Thi (The journal of contemporary issues in business and government, 2022)
In the digital era, to satisfy the continuously increasing demand of the customer, businessesmust enhance their competitiveness through factors such as price, service quality, image prestige.... In Vietnam, postal is considered an essentialand potential service sector, contributing significantly to the State budget and creating jobs for workers. This research aims to analyze the factors influencing the competitiveness of postal enterprises in Vietnam. The study was based on the 316 postal enterprises in Hanoi and Ho Chi Minh City; the research hypotheses were examined by structural equation modeling (SEM). The results revealed that six factors: Financial Capacity, Services Capacity, Network development capacity, Integration capacity, Organizational and management capacities, The ability to apply science & technology, machinery & equipment utilization all positively affect the competitiveness of postal enterprises. In which, Services Capacity has the strongest influence on the competitiveness of Vietnamese postal enterprises.These research results have practical significance in helping Vietnamese postal enterprises improve their competitiveness.